PERAN ZAKAT SEBAGAI INSTRUMEN PENGENTASAN KEMISKINAN - Zein, Aliman Syahuri (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2016)
AbstractPoverty is a big problem facing Indonesia. From the viewpoint of Islam, Allah Swt forbid poverty.Poverty occurred originated from inequality of wealth distribution.Therefore, Islam emphasizes equitable economic distribution arrangements that inequality in society can be overcome.One way to do this is by implementing zakat.Various obstacles in the application of zakat, namely; lack of knowledge and understanding of the community resulted in a lack of awareness and the desire to remove zakat, lack of public trust in zakat management institutions, zakat laws that are not fully able to be implemented correctly, zakat less professional. Therefore, it needs to be disseminated to change the way people view zakat, improvement of inter-agency coordination charities,innovation in the distribution patterns of zakat funds, Professional managers, and changes in distribution patterns towards more productive zakat.Kata Kunci: zakat, poverty, OPZ